A Further Look at Reading the Mind in the Eyes-Child Version: Association With Fluid Intelligence, Receptive Language, and Intergenerational Transmission in Typically Developing School-Aged Children - Rosso, Anna Maria; Riolfo, Arianna (Frontiers in Psychology, 2020)
A number of tasks have been developed to measure the affective theory of mind (ToM), nevertheless, recent studies found that different affective ToM tasks do not correlate with each other, suggesting that further studies on affective ToM and its measurement are needed. More in-depth knowledge of the tools that are available to assess affective ToM is needed to decide which should be used in research and in clinical practice, and how to interpret results. The current study focuses on the Reading the Mind in the Eyes Test (RMET) primarily to investigate in a sample of 112 children the currently unexplored relationships in middle childhood between performance on the RMET and fluid intelligence. Relationships with receptive vocabulary, age, and sex were also investigated. Moreover, because studying the family’s influence on children mentalization could have important implications in developing prevention and treatment interventions, this study offers a novel contribution to the field by exploring the family’s influence on children’s RMET performance. Although significant positive correlations were found among RMET-C performance, fluid intelligence, and receptive language, regression analysis revealed that fluid intelligence was the only predictor. No family influence was found on children’s RMET performance. On the whole, results from the current study offer some support to the hypothesis that RMET-C is not a “pure” ToM task, specifically the effect of fluid intelligence on RMET performance should be taken into account when RMET is used both in research and in the clinical setting.